A Clot to Uncover: FOXP3 and SARS-CoV-2 Nucleocapsid Interactions and Their Effect on DNA Binding - Mcinnes, Keiran (University of the Witwatersrand, Johannesburg, 2024)
During COVID-19, systemic coagulopathy, which can lead to strokes and embolisms, is often observed in COVID-19 patients and may also contribute to long COVID. This coagulopathy is the result of overactivated platelets in circulation that leads to inappropriate clot formation. FOXP3 is a transcription factor involved in platelet development and loss of FOXP3 function leads to platelets that resemble those seen during COVID-19. Thus, FOXP3 may be dysregulated in COVID-19. The SARS-CoV- 2 nucleocapsid (NC) is a multifunctional protein typically associated with viral genome packaging and virion assembly. However, it is also capable of binding DNA and is potentially able to alter regulation of host protein expression. Here, potential interactions between the DNA-binding forkhead domain (FHD) of FOXP3 and the SARS-CoV-2 NC were investigated. Identification of a novel interaction between FOXP3 and SARS CoV-2 NC may provide new clues as to the pathophysiology of COVID-19. To address this aim, both proteins were overexpressed in T7 E. coli, purified via immobilised metal affinity chromatography, and monitored for potential interactions in the absence and presence of DNA using pull-down assays and fluorescence anisotropy. A direct interaction was identified between the two proteins in the absence of DNA. Additionally, it was found that both proteins are capable of binding to DNA at the same time, but excess NC was found to cause FHD dissociation from the FHD- NC-DNA complex. This result implicates NC in FOXP3 dysfunction which may be associated with the coagulopathy and other symptoms seen during COVID-19. Additionally, NC DNA binding does not appear to be driven by the FOXP3 consensus sequence, indicating that FOXP3 may not be the only transcription factor potentially dysregulated by NC
A Dissertation Submitted in fulfillment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa 2024
Keywords: COVID-19; Coagulopath; FOXP; DNA; SDG-3: Good health and well-being